The Comprehensive Systematic Review of Platelet Count and Hematocrit as Predictors of Plasma Leakage in Dengue Hemorrhagic Fever - Hairanty sinaga; Cici Nurhalimah (The International Journal of Medical Science and Health Research, 2026)
Introduction: Dengue hemorrhagic fever (DHF) remains a major public health concern in endemic regions, with plasma leakage being the pathognomonic feature determining disease severity. Despite widespread clinical use of platelet count and hematocrit as monitoring parameters, their predictive value for plasma leakage remains debated. This systematic review aims to comprehensively evaluate the evidence for platelet count and hematocrit as predictors of plasma leakage in DHF patients. Methods: A systematic review of 34 sources including primary observational studies, systematic reviews, meta-analyses, and randomized controlled trials was conducted. Studies were screened based on predefined criteria including DHF population according to WHO criteria, plasma leakage assessment through clinical signs or imaging, reporting of platelet count and/or hematocrit as predictors, and adequate statistical information. Data extraction encompassed study characteristics, platelet and hematocrit measurements, statistical findings, and confounding factors. Results: Low platelet count demonstrated consistent association with plasma leakage across multiple meta-analyses, with pooled odds ratios ranging from 2.01 (95% CI: 1.70-2.38) to 3.21 (95% CI: 1.81-5.69). A dose-response relationship showed 33% increase in logOR per 10,000-cell decrement. Platelet count below 50,000/mm³ was identified as a significant threshold for dengue shock syndrome (OR=2.85; 95% CI: 1.25-6.47). Hematocrit showed variable predictive utility depending on measurement timing; significant during critical phase (days 4-7) but not during early febrile phase. Combined assessment of rising hematocrit with declining platelet count yielded the strongest predictive signal (OR range: 5.13-43.17). Discussion: The apparent contradiction regarding hematocrit's predictive value is explained by temporal discordance in measurement timing. Platelet count emerges as a more reliable early predictor, with reductions detectable during febrile phase before hemoconcentration manifests. Population-specific factors, particularly age, significantly modulate predictive accuracy. The combined parameter approach captures mechanistically linked processes of capillary permeability and platelet consumption. Conclusion: Platelet count below 50,000/mm³ and rising hematocrit (particularly >20% above baseline) are consistent predictors of plasma leakage, with combined assessment providing optimal predictive utility. Serial monitoring rather than single-point measurements is essential. Future research should focus on developing integrated predictive models incorporating clinical, laboratory, and sonographic parameters.